Fade into the Shadows: Adjustments in Administrative Divisions and Regional Disparities - Yangyang Jie; Peikang Zhang; Tiyan Shen (Global Labor Organization (GLO), 2025)
Institutional changes have a significant impact on government capabilities and hierarchical relationships, especially in developing countries that characterized by governmental intervention for regional development. Using data from China's districts and counties from 1993 to 2022, this paper examines how administrative division adjustments, exemplified by the re-designation of counties as city districts, redefine the power and capability dynamics among bureaucratic entities. We find evidence that such redesignations widen regional disparities between transformed counties and other areas in four dimensions, including economic output, financial resources, fiscal capacity, and public services. We further identify three key mechanisms: reduce autonomy for former county governments, local government competition that leads to short-term efficacy, and resource siphoning from former counties to other regions. The effectiveness of the policy depends on changes in central policies, particularly on the trade-off between scale and incentives.
Keywords: H11; H77; R12; 330; Regional disparity; Administrative division adjustment; Autonomy; Power structure